2012
DOI: 10.4049/jimmunol.1102543
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NLRP3 Inflammasome by Group B Streptococci

Abstract: Group B streptococcus (GBS) is a frequent agent of life-threatening sepsis and meningitis in neonates and adults with predisposing conditions. We tested the hypothesis that activation of the inflammasome, an inflammatory signaling complex, is involved in host defenses against this pathogen. We show here that murine bone marrow-derived conventional dendritic cells responded to GBS by secreting IL-1β and Il-18. IL-1β release required both pro-IL-1β transcription and caspase-1-dependent proteolytic cleavage of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(152 citation statements)
references
References 47 publications
6
140
4
1
Order By: Relevance
“…We also showed that GBS induces IL-1␤ production in an NLRP3-dependent manner in dendritic cells (13). In this study, we demonstrate that GBS activates the NLRP3 inflammasome by a mechanism that requires hemolysin-mediated lysosomal leakage.…”
mentioning
confidence: 57%
“…We also showed that GBS induces IL-1␤ production in an NLRP3-dependent manner in dendritic cells (13). In this study, we demonstrate that GBS activates the NLRP3 inflammasome by a mechanism that requires hemolysin-mediated lysosomal leakage.…”
mentioning
confidence: 57%
“…[40][41][42] Viral nucleic acids are usually detected by the retinoic acidinducible gene 1 and AIM2-like receptor (ALR) inflammasomes; however, several viruses and their components, including influenza virus (the proton-selective ion channel protein M2), 43 encephalomyocarditis virus (viroporin 2B), 44 poliovirus and enterovirus 71 (non-structural 2B protein), 44 rhinovirus (2B proteins), 45 human respiratory syncytial virus (small hydrophobic protein), 46 are sufficient to stimulate NLRP inflammasome activation. Recent studies have revealed a crucial protective role of inflammasome activation during viral infection, via an increase in adaptive immune activation with limited tissue damage.…”
Section: Pamp Signals That Activate the Nlrp3 Inflammasomementioning
confidence: 99%
“…6 NLRP3 inflammasome is activated by a diverse set of stimuli, but, classically, it is associated to the sensing of noxious agents as monosodium urate crystals (associated to gout) and extracellular ATP, particles as silica and asbestos, and also pathogens. 7 Among infectious agents, bacteria, as Streptococcus agalactiae 8 ; viruses, as Rift Valley fever virus 9 ; protozoans, as Plasmodium berghei 10 and fungi, as Candida albicans 11 were shown to activate this system. This multitude of potential activators places NLRP3 as a prominent actor in many diseases associated to inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%